(untitled) (Research, Society and Development, 2022)
Changes in the structure of the normal aorta are related to the development of clinical diseases, such as abdominal aortic aneurysm. An aneurysm is an abnormal expansion of the aorta, which is located in the blood vessels and heart and involves three outer garments. In the aorta, compared to the proximal part, the diameter of the blood vessel corresponding to the AAA increases about 50%. As AAA is most often asymptomatic and has high mortality due to rupture, early recognition and elective surgical correction are the best strategies to prevent death. Thus, this review aims to expose through the analysis of scientific articles the importance of early diagnosis of patients with abdominal aortic aneurysm. This is a systematic qualitative bibliographic review, carried out between 2017 and 2021 in Portuguese, English and Spanish. Some recent studies on the incidence of abdominal aortic aneurysms seem to indicate that progress in treating these patients is increasing. The reason for this favorable evolution must be attributed to the measures of early diagnosis of patients at risk, fundamentally performed by ultrasonography. It is necessary to use early diagnosis in patients who are at risk of developing AAA, since elective surgical management has allowed a considerable reduction in mortality. Studies are also needed to develop a pharmacological treatment that proves to be effective in delaying the progression and rupture of these aneurysms.